Mapping the Archaeological Continuum Filling 'Empty' Mediterranean Landscapes - Campana, Stefano R.L (SpringerBriefs in Archaeology,, 2018)
This book addresses the true 'landscape' perspective approach that archaeologists in Italy, and in many parts of the Mediterranean, use to study the archaeology of landscapes, marking a departure from the traditional site-based approach. The aim of the book is to promote the broader application of new paradigms for landscape analysis, combining traditional approaches with multidisciplinary studies as well as comparatively new techniques such as large-scale geophysical surveying, airborne laser scanning and geo-environmental studies. This approach has yielded tangible and striking results in central Italy, clearly demonstrating that identifying the 'archaeological continuum' is a realistic aim, even under the specific environmental and archaeological conditions of the Mediterranean world.